The Effect of Digital Picture Series Media on Simple Essay Writing Skills in Elementary Schools - Trisna Aulia; Vevy Liansari (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to determine the effect of digital series picture media on simple essay writing skills in the Indonesian language subject for third-grade students at SDN Tawangrejo II Pandaan, classified as low. The research method used in this study is quantitative with a pre-experimental design, specifically the one-group Pre-Test-Post-Test design. The subjects of this study were 32 third-grade students. The sampling technique used in this study was saturated sampling. The data collection technique used in this study was a test to measure third-grade students' simple essay writing skills. The test was conducted with a Pre-Test and a Post-Test. The test consisted of writing a simple essay based on five indicators. The data analysis technique differed significantly between the Pre-Test and Post-Test results. This was indicated by the hypothesis test using the paired sample t-test with a significance value of 0.000, which means the sig value < 0.05. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The use of digital series picture media significantly affects simple essay writing skills.